More than medals : a history of the Paralympics and disability sports in postwar Japan - Frost, Dennis J. (Cornell University Press, 2020)
"Exploring how sports have shaped perceptions of and approaches to disability in postwar Japan, this book examines five international sporting events held in Japan for athletes with disabilities: the 1964 Tokyo Paralympics, the FESPIC Games, the Ōita International Wheelchair Marathon, the 1998 Nagano Winter Paralympics, and the Tokyo 2020 Paralympics"--